Software services protection security protocol based on software watermarking in cloud environment - Jin-chao XU; Guo-sun ZENG; Wei WANG (Tongxin xuebao)
Aimed to resist the infringement of software services in cloud environment,a software services protection security protocol based on software watermarking in cloud environment was presented.On the consideration of actual needs in cloud computing,the protocol introduced the software watermarking as a service cloud which was responsible for software watermark embedding and extraction.The protocol not only met the basic requirements of software copyright protection,but also gived the detailed strategy to solve the infringement,and hardened the ability of the software watermarking to resist various attacks.The analysis shows that the proposed protocol has higher security.